Implementasi Aplikasi Penjualan Jasa Followers Berbasis Website - Muhammad Fahrel Abimanyu; Edy Rahman Syahputra; Arie Rafika Dewi (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of information technology that encourages each individual to think creatively and innovatively to keep up with the times. Thus in the field of sales of followers, currently sales followers are in great demand by the public. This process of adding followers aims to increase brand awareness and trust in what products they sell on their social accounts. Customer convenience can increase satisfaction in purchasing. This is an opportunity for the author to build and design an online web-based follower sales application that is able to simplify the ordering process without waiting long for the order. This application makes it easier for customers to make the ordering process without coordinating with the admin first, so research is carried out that aims to find out how to design and implement a web-based sales information system. The method used is SDLC Waterfall model which consists of requirements analysis, design, code generation, testing, implementation and maintenance. The result of this research is that the existence of a web-based sales information system can make marketing more focused without having to compete with competitors on one platform and is expected to increase sales.